PEMIKIRAN IBNU TAIMIYAH TENTANG STANDART HARGA JUAL DAN BELI DALAM KITAB AL-HISBAH - Huddin, Misba; Fahmi, Muhammad Zainul Arifin (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2025)
This research focuses on Ibn Taimiyyah's thoughts on price standards found in the book Al-Hisbah. The selection of Ibn Taimiyyah for this research is due to his thoughts and prominence in the field of economics, which are indeed relevant to current conditions, especially regarding prices and market mechanisms amidst increasingly uncertain market conditions. This research employs a qualitative method with a narrative approach, as it investigates the thoughts of the figure by using the book Al-Hisbah as primary data and also other works by Ibn Taimiyyah as secondary data analyzed through content analysis techniques. The results obtained from this study indicate that the pricing of goods must be in accordance with the natural market mechanisms determined by the equilibrium between supply and demand; however, under certain conditions, the government must also take part in determining prices to ensure that they remain stable and fair for all parties.